2007
DOI: 10.1016/j.enpol.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple calibration decomposition analysis: Energy use and carbon dioxide emissions in the Japanese economy, 1970–1995

Abstract: The purpose of this paper is to present a new approach to evaluating structural change of the economy in a multisector general equilibrium framework. The multiple calibration technique is applied to an ex post decomposition analysis of structural change between periods, enabling the distinction between price substitution and technological change to be made for each sector. This approach has the advantage of sounder microtheoretical underpinnings when compared with conventional decomposition methods. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…While Okushima and Tamura [13] is a comprehensive study of changes in energy use and carbon dioxide emissions in the Japanese economy from 1970 to 1995, this paper centers on the change in industrial energy use, especially energy-intensive industry, in the 1970-1990 period. This period includes two oil crises: one in 1973 and a second in 1979.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While Okushima and Tamura [13] is a comprehensive study of changes in energy use and carbon dioxide emissions in the Japanese economy from 1970 to 1995, this paper centers on the change in industrial energy use, especially energy-intensive industry, in the 1970-1990 period. This period includes two oil crises: one in 1973 and a second in 1979.…”
Section: Resultsmentioning
confidence: 99%
“…This section outlines a new decomposition methodology -the Multiple Calibration Decomposition Analysis (MCDA)-originally proposed by Okushima and Tamura [13]. The method explicitly defines two-tier constant elasticity of substitution (CES) production functions as an underlying model to separate price substitution effects from other types of technological change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology plays an important role in reducing CO2 emissions in the production process. Okushima and Tamura [20] found that technological change is of great importance for curtailing energy use and CO2 emissions in Japan. They argued that CO2 emissions increased during 1970-1995 primarily because of the economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%